Water clear cell ectopic non-iatrogenic giant parathyroid adenoma in sternohyoid muscle with thyroid nodule and asymptomatic hypercalcemia due to primary hyperparathyroidism: Case report and literature review. (September 2021) - Mohamed, Walla; El Ansari, Walid; Al Hassan, Mohamed S.; Sibira, Rayan M.; Abusabeib, Abdelrahman
Abstract: Background: Ectopic parathyroid gland is not uncommon, and is associated with primary hyperparathyroidism. Giant parathyroid adenoma (PA) and concurrent presence of enlarged thyroid nodule increases the probability of ectopic location. The combination of a giant PA that is ectopic (within the strap muscle) in the neck is very rare, especially in cases with no previous surgery. The rare histopathological findings of the current case, water clear cell parathyroid adenoma (WCCPA), could explain the patient's presentation, since it has low endocrine function. Case presentation: A 56-year-old Qatari female on routine visit to primary health care physician for hypertension, was incidentally discovered to be hypercalcemic and was referred to the emergency department of our institution. Neck ultrasound showed a thyroid nodule on the left side, but 99m Tc-sestamibi scintigraphy identified a left PA. FNAC of the thyroid nodule showed that it was a colloid nodule. She underwent left hemithyroidectomy and excision of left PA. Intraoperatively, the PA was giant and in the sternohyoid muscle. Intraoperative monitoring of intact PTH (IOiPTH) confirmed successful excision. Discussion: Ectopic giant parathyroid adenoma is rare especially with the intramuscular location in sternohyoid muscle in the neck without previous neck surgeries. The presence of thyroid nodule could be a precipitating factor for migration of the PA. Preoperative assessment with the radiological image is crucial for diagnosis but sometimes fail to localized the PA. Conclusion: Giant asymptomatic PA with long standing low function before hyperfunctioning should raise the suspicion of WCCPA. If diagnosis is confirmed, metastasis from a clear cell renal cell carcinoma should be ruled out. Highlights: We report a unique rare case of non-iatrogenic ectopic giant water clear cell parathyroid adenoma (WCCPA) A parathyroid adenoma >3.5 gm, asymptomatic and with low function before hyperfunctioning, should raise suspicion of WCCPA. History, examination, ultrasound, sesta-MIBI scintigraphy and immunohistochemical studies are important for diagnosis. High preoperative parathyroid hormone and calcium need monitoring in post-operative period to avoid hypocalcemia.